Role Of Public-Private Partnership In Improving The Economy Through Tourism Development At Disporapar Balikpapan City - Abdulloh, Abdulloh; Markhamah, Siti; Soesilowati, Etty (IJBLE Scientific Publications Community Inc., 2023)
Public-Private Partnership (PPP) is a collaboration between the government and the private sector in planning, funding, building, managing or providing public services, this is also carried out by the Balikpapan City Dispporapar Service to improve the economy through tourism development. This research aims to describe and analyze the implementation of government partnerships through the Balikpapan City Disporapar and private parties in tourism development and the benefits for the surrounding community by looking at the output and outcomes of the existing partnerships. The method used in this research is qualitative with data collection using observation techniques, in-depth interviews and documentation. Informants were determined using a purposive sampling technique that was adapted to data needs. The public-private partnership variable is seen from several aspects, namely implementation, community empowerment, technical guidance with partners and commercialization. The data analysis technique uses interactive analysis from Miles and Hubberman which consists of data reduction, data presentation and conclusion. The results of the research show that the implementation of the Public Private Partnership between the Balikpapan City Disporapar and the private sector is through a CSR (Corporate Social Responsibility) funding scheme and a cooperation agreement scheme, then the Balikpapan City Disporapar and Tourism also provides technical guidance so that tourism development can be optimal for the actors. businesses operating in the tourism sector and young entrepreneurs, the impact of PPP on improving the economy of communities around tourist destinations in Balikpapan City, namely creating new business opportunities in the tourism sector, creating local economic development and increasing community income